STUDI KOMPARASI PEMBELAJARAN SENI LUKIS PADA EKSTRAKURIKULER DI SD IT AZ-ZAHRA DAN SD NEGERI BINTORO 04 KABUPATEN DEMAK - Lutfiyah, Ana Rofatul; Rofian, Rofian; Arisyanto, Prasena (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
This research aims to find out the management management system, administration and extracurricular learning of painting art at SD IT Az-Zahra and SD N Bintoro 04 in encouraging the success of learners in the competition